Participatory Development of Model Communities to Support the Aging Society in the Isan Context - Kankarn, Waratip; Wirunphan, Botsaporn; Arthiwet, Wilawan; Thajai, Sumalee (Journal of The Royal Thai Army Nurses, 2023)
This study was a participatory action research. Model community development to support the aging society in the Isan context intended for 1) Study the context and community participation to support the aging society 2) Develop community participation activities to support the aging society 3) The effectiveness of activities supporting the aging society 4) Evaluate and improve in accordance with the community context. Qualitative and quantitative data collection. Data were collected by interviews, focus groups and questionnaires. Quantitative data were analyzed using frequency, percentage, mean and standard deviation, comparative statistics and qualitative data by content analysis. The study found that community participation and the work of strong network partners in the area in co-thinking, doing, co-learning and jointly develop operations to support the aging society in doing activities that are beneficial to the social community in order to develop the elderly to have the potential to lead a valuable, happy, self-reliant life sustainably and arising under the existing social capital in the community. The elderly who participated in the activity had quality of life increased in 4 dimensions: physical, mental, social relations, and environment.